2017
DOI: 10.1155/2017/3860674
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Autoimmune Diabetes and Poor Glycaemic Control among Adults in Madagascar: A Brief Report from a Humanitarian Health Campaign in Ambanja

Abstract: Madagascar is a geographically isolated country considered a biodiversity hotspot with unique genomics. Both the low-income and the geographical isolation represent risk factors for the development of diabetes. During a humanitarian health campaign conducted in Ambanja, a rural city in the northern part of Madagascar, we identified 42 adult subjects with diabetes and compared their features to 24 randomly enrolled healthy controls. 42.9% (n = 18) of diabetic subjects showed HbA1c values ≥ 9.0%. Unexpectedly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Patients with LADA are at high risk of progression to insulin dependency . LADA accounts for 2.6% to 12% of all patients with diabetes, which differs significantly in different ethnic groups . Our previous study has shown that around 5.9% of diabetic patients were classified as LADA in China .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with LADA are at high risk of progression to insulin dependency . LADA accounts for 2.6% to 12% of all patients with diabetes, which differs significantly in different ethnic groups . Our previous study has shown that around 5.9% of diabetic patients were classified as LADA in China .…”
Section: Introductionmentioning
confidence: 98%
“…2 LADA accounts for 2.6% to 12% of all patients with diabetes, which differs significantly in different ethnic groups. [3][4][5][6] Our previous study has shown that around 5.9% of diabetic patients were classified as LADA in China. 7 According to the population epidemiological survey, it can be speculated that China has the largest number of LADA patients, which are more than 6 million.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a heterogeneous disorder consisting of several disease subgroups showing different behaviours and outcomes. 1,2 While the great majority of cases are type 2 diabetes, a proportion varying from 2% to 12% of people with adult-onset diabetes are affected by latent autoimmune diabetes in adults (LADA), 3,4 a slowly progressive form of autoimmune diabetes with similarities and differences from both type 1 and type 2 diabetes. 5 The comparative evaluation of complications between different forms of diabetes is an open research area, with possible implications for the comprehension of complications' pathogenesis, risk stratification and individualized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…It is also uncertain whether CV risk factors for macrovascular complications contribute equally in T1D and T2D . Autoantibodies (AAb) to islet‐cell cytoplasm (ICA), to glutamic acid decarboxylase (GADA) or to islet antigen‐2/2ß (IA‐2A) are detectable in up to 12% of adults with a clinical diagnosis of T2D . The presence of these AAbs identifies a subset of patients who have latent autoimmune diabetes in adults (LADA).…”
Section: Introductionmentioning
confidence: 99%
“…3 Autoantibodies (AAb) to islet-cell cytoplasm (ICA), to glutamic acid decarboxylase (GADA) or to islet antigen-2/2ß (IA-2A) are detectable in up to 12% of adults with a clinical diagnosis of T2D. 4,5 The presence of these AAbs identifies a subset of patients who have latent autoimmune diabetes in adults (LADA). LADA patients tend to be leaner and younger and to have a healthier CV risk profile than individuals without LADA.…”
mentioning
confidence: 99%